The Effect of Go Composition Variation on The Optical Properties of ZnO/GO Thin Films as a Candidate Material for Solar Cells - Maharani, M; Jonuarti, Riri; Ratnawulan, R; Hidayat, Rahmat (PILLAR OF PHYSICS, 2025)
This study aims to investigate the effect of Graphene Oxide (GO) composition variation on the optical and electronic properties of ZnO/GO thin films, which have potential as candidate materials for solar cells. The synthesis method employed is sol-gel, followed by the spin coating technique to produce thin films on glass substrates. Characterization was carried out using X-Ray Diffraction (XRD) to determine the crystalline structure, Scanning Electron Microscopy (SEM) for morphological analysis, and UV-Vis spectroscopy to measure optical properties, including light absorption and band gap.  The results indicate that a 3% GO composition significantly affects the optical and electronic properties of ZnO/GO. The addition of GO enhances light absorption in both the UV and visible ranges and reduces the band gap, contributing to improved energy conversion efficiency. Furthermore, SEM characterization shows a better particle distribution at 3% GO compared to other compositions, enhancing the interaction between ZnO and GO. Based on these findings, it can be concluded that a ZnO/GO combination with 3% GO has good potential as a material for solar cell applications. This research is expected to contribute to the development of more efficient and environmentally friendly renewable energy materials